2022
DOI: 10.1111/jcms.13346
|View full text |Cite
|
Sign up to set email alerts
|

That's an Order! How the Quest for Efficiency Is Transforming Judicial Cooperation in Europe

Abstract: Effective procedural arrangements allow courts to reconcile conflicting demands of timely justice and sound legal argument. In the context of the European Union, conflict between these demands emerged most acutely in the face of paralyzing delays in the preliminary reference procedure. It was partly solved by Article 99 of the Rules of Procedure. The provision allowed the European Court of Justice to dispose of repetitive and legally undemanding cases with a reasoned order in lieu of a judgment. This article a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…They shed new light into the relation of the Court and its interlocutors, by pointing to differentiated strategies in using deference. Finally, adding to recent literature on the use of other procedural tools at the Court (Brekke et al, 2023;Šadl et al, 2022), the findings suggest a willingness of the Court to encourage a more active participation of national courts in the dialogue of the preliminary reference procedure.…”
Section: Is Deference Used Strategically As a Resilience Technique By...mentioning
confidence: 72%
See 1 more Smart Citation
“…They shed new light into the relation of the Court and its interlocutors, by pointing to differentiated strategies in using deference. Finally, adding to recent literature on the use of other procedural tools at the Court (Brekke et al, 2023;Šadl et al, 2022), the findings suggest a willingness of the Court to encourage a more active participation of national courts in the dialogue of the preliminary reference procedure.…”
Section: Is Deference Used Strategically As a Resilience Technique By...mentioning
confidence: 72%
“…The Court has no docket control so, unless withdrawn by the referring court, all referred questions must receive an answer in a judgment or order. The Court increasingly issues reasoned orders instead of judgments to respond to superfluous references (Brekke et al, 2023). These orders require fewer resources and substantially decrease the processing time at the Court (Šadl et al, 2022).…”
Section: Alternative Accountsmentioning
confidence: 99%
“…These judges had all decided against referrals because they worried that the CJEU is overburdened with cases and unable to deliver judgements within a reasonable time. Previous research has suggested that the CJEU harbours similar concerns about the long processing time in the preliminary ruling procedure (Brekke et al, 2022). One of the interviewees stated, If all courts of final instance were to ask questions, which they are obliged to do as soon as doubts arise, then the European Court of Justice would be drowning in requests for preliminary rulings.…”
Section: Motives For (Not) Requesting Preliminary Rulingsmentioning
confidence: 99%